I'm not at work, but I am not absent - Bynoe, Andraa M. (2008)

(untitled)
This study focuses on employees perceptions of absenteeism in Carlton Supermarket, Barbados. Absenteeism is now formally being recognised as a national problem in Barbados and there is limited research on absenteeism in Barbados. This study aims to add to the body of research by attempting to present some understanding of the absence phenomenon within Carlton Supermarket. This will be done from an interpretive research approach.